Multifaced roles of adipokines in endothelial cell function - Yan, Yu; Wang, Lihui; Zhong, Ni; Wen, Donghua; Liu, Longhua (Frontiers in Endocrinology, 2024)
Obesity significantly contributes to the progression of cardiovascular diseases (CVDs) and elevates the risk of cardiovascular mortality. Atherosclerosis, the primary pathogenic process underlying CVDs, initiates with vascular endothelial dysfunction, serving as the cornerstone of vascular lesions. Adipokines, bioactive molecules secreted by adipose tissue that regulate metabolic and endocrine functions, play a pivotal role in modulating endothelial function during atherosclerosis. This review comprehensively examines the distinct roles of various adipokines in regulating endothelial function in atherosclerosis. We categorize these adipokines into two main groups: protective adipokines, including adiponectin, FGF21, CTRP9, PGRN, Omentin, and Vaspin, and detrimental adipokines such as leptin, Chemerin, Resistin, FABP4, among others. Targeting specific adipokines holds promise for novel clinical interventions in the management of atherosclerosis-related CVDs, thereby providing a theoretical foundation for cardiovascular disease treatment strategies.